Negative Mass & Astrotheology (British Journal of Multidisciplinary and Advanced Studies, 2022)
In this paper, we speculate about the beginnings of God and His universe. We use familiar calculations from AT Math that indicate that God began when the unphysical universe began. Mass appeared at t=1/2 E=-1.25. We show that Quantum Mechanics may be probabilistic but predictable.